Specific Myocardial Lesion in a Patient with Diffuse Large B-Cell Lymphoma (a Case Report) - D. D. Sakaeva; T. V. Raevskaya; Ch. Kh. Valiakhmetova; A. I. Iskhakova (Креативная хирургия и онкология, 2019)
Introduction. Myocardial lymphoma is one of the rarest lesion localizations among all the lymphoproliferative diseases. Regardless of the current lack of generally accepted specific recommendations for the treatment of primary and secondary myocardial lymphomas the chemotherapy is carried out in accordance with clinical guidelines for the treatment of lymphoproliferative diseases, which in some cases results in a successful outcome.Materials and methods. The article presents a clinical example of the diagnostic procedure and treatment of a 65-year-old female with the following diagnosis: non-Hodgkin’s lymphoma st. II BE gr. II with the involvement of myocardium, cervical and mediastinal lymph nodes, and the right palatine tonsil. The patient received six courses of R-CEOP chemotherapy.Results and discussion. An echo-positive structure 28mm by 20 mm in size attached to the interatrial septum was found inside the right atrium following the second course of chemotherapy. Ejection fraction: 61%. Effect: regression exceeding 50%. Four months following the completion of treatment the ejection fraction was 63%, regression – exceeding 80%, thus implying a partial response.Conclusion. The diagnosis of lymphoma with a lesion in the myocardium has been positively verified by histology and IHC. Currently less invasive techniques are normally preferred, transesophageal cardiac echo guided biopsy being one. Similar to any other lymphoproliferative disease, myocardial lymphoma is a chemosensitive tumour that responds well to treatment. In each individual case, the treatment strategy must be patient-specific and take into account the somatic status of the patient, the tumour size and the degree of its spread, the tumour morphological type, and whether it would be possible to arrange adequate specialized support needed.